Modeling the instantaneous response of glaciers after the collapse of the Larsen B Ice Shelf. Issue 13 (7th July 2015) - De Rydt, J.; Gudmundsson, G. H.; Rott, H.; Bamber, J. L.
Abstract Following the disintegration of the Larsen B Ice Shelf, Antarctic Peninsula, in 2002, regular surveillance of its ∼20 tributary glaciers has revealed a response which is varied and complex in both space and time. The major outlets have accelerated and thinned, smaller glaciers have shown little or no change, and glaciers flowing into the remnant Scar Inlet Ice Shelf have responded with delay. In this study we present the first areawide numerical analysis of glacier dynamics before and immediately after the collapse of the ice shelf, combining new data sets and a state‐of‐the‐art numerical ice flow model. We simulate the loss of buttressing at the grounding line and find a good qualitative agreement between modeled changes in glacier flow and observations. Through this study, we seek to improve confidence in our numerical models and their ability to capture the complex mechanical coupling between floating ice shelves and grounded ice.